TRIAD AND MODUS MODEL REALIZATION OF POTENTIAL ENERGY AND RESOURCE SAVINGS ON THE ENTERPRISES - Klimchuk , M.M. (The actual problems of regional economy development, 2017)
The article studied categories of the resource, energy and potential energy savings that resulted in the development of triad and modus model of potential energy and resource savings enterprises based on the concept of “environmental economics”. To assess the level of energy efficiency in the company it is proposed to use a definition of “potential of energy and resource savings” which is interpreted as a synergistic approach to improve energy conservation reserves through intensification of production based on the rationalization of the use of all resources.